INTERCULTURAL FRIENDSHIP AS STRATEGY TO REDUCE ANXIETY AND UNCERTAINTY OF ZIMBABWE STUDENTS IN MUHAMMADIYAH SURAKARTA UNIVERSITY - Khusnul Khatimah; Rina Sari Kusuma (Universitas Muhammadiyah Surakarta, 2019)
Friendship is a relationship between voluntarily wounded individuals. Friendships have a responsibility to be emotionally supportive, actively provide assistance, maintain confidence, and support each other. Benefit in friendship usually include skills in activity, emotional support and help. Intercultural friendship is a more specific and more complex phenomenon that has its own characteristics in terms of relationships. The meeting between two different cultures in building a relationship of intercultural friendship. Establish intercultural friendship relationships with local people by immigrants as a form of adaptation to the new environment. Immigrants are individuals who move from one region to another in a country influenced by push factors and pull factors such as economic, environmental, and educational factors. Immigrants can experience several conditions when they are in a new environment such as feelings of anxiety and uncertainty to interact with the surrounding environment. This study aims to find out how the relationship of intercultural friendship can reduce the level of anxiety and uncertainty of Zimbabwean students at the Muhammadiyah Surakarta University. The research method used qualitative method by using population from foreign students at Muhammadiyah Surakarta University and purposive sampling technique that is sampling based on student's country of origin Zimbabwe. Data collection by interview and documentation, for analysis using qualitative content analysis. Credibility and validity use inter-code reliability and triangulation of data sources and theories.Keywords : Adaptation, Migration , Anxiety, Uncertainty, Intercultural, Friendship.